The benefits of physical exercise for older women: a comparison between two different modalities - Rafaela Korn; Marilda Morais da Costa; Mauren da Silva Salin; Fabrício Noveletto; Yoshimasa Sagawa; Antonio Vinicius Soares (Academia Medicine)
Population aging, characterized by increased life expectancy and reduced birth rates, poses significant challenges for the health and functionality of older adults. Sedentary behavior is an aggravating factor, as it is associated with the development of chronic diseases, loss of autonomy, and higher mortality. In contrast, regular physical activity improves the quality of life of older adults, delaying the onset of disabling conditions and promoting physical, psychological, and social benefits. This study aimed to compare body composition and physical performance in older women who practiced two types of physical exercise: aerobic training (AT) and strength training (ST). Both groups benefited from the exercise modalities, but the ST group showed superior results, particularly in terms of body composition, muscle strength, and functional performance (p < 0.05). Muscle strength, in particular, stood out as the most important physical ability, showing a strong correlation with functionality. These findings emphasize the importance of strength training as an effective strategy for promoting health and independence in the elderly population.